Mouth Corset Vibration Berbasis Sinyal Frekuensi Penggetar Sebagai Alat Terapi Pada Penderita Pasca Stroke Ringan - Setiahawati Setiahawati; Monica Merry Febriyana; Zulfandi Zulfandi; Zahra Ayu Damayanti; Irnin Agustina Dwi Astuti (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2021)
Stroke is a disorder that attacks the functional organs of the brain in the form of nerve paralysis (neurological deficit) due to the cessation of blood supply to the brain. One of the treatments that can be done is by doing facial massage in the form of vibration, since this treatment can mechanically stimulate important internal organs and can physiologically can stimulate autonomic (unconscious) nervous system in internal organs through external actions. Using latest innovations, we present an equipment we like to call "Mouth Corset Vibration." The Mouth Corset Vibration is used to improve oral posture by flexing the nerves using a vibrating frequency signal as a therapeutic tool in patients with mild post-stroke. In the current state of the COVID-19 pandemic, this mouth corset is expected to be able to provide a faster, affordable and efficient method of recovery at home. This equipment is also suppoied with an integrated smartphone module to monitor the duration of the therapy.